A Causal Review of Dynamics in Indian Ports. (January 2019) - Sinha, Deepankar; Bagodi, Virupaxi
India has about 200 ports along its coastline, which is about 7, 500 kilometres long. However, none of these ports feature in the world's top 20. Several studies on port efficiency indicate the need to benchmark the productivity of ports with global standards. Productivity is measured in terms of cargo (in tonnes, or 20-foot equivalent unit, TEU) handled per hour or so. The outcome of enhanced productivity is quicker turnaround time of ships. The productivity of the major Indian ports does not match the global standards. In order to improve their efficiency, the government-managed ports have initiated privatization of their terminals and outsourcing of cargo handling services since 1991. Yet, the ports are lagging behind major ports across the world. A major reason for the inefficiencies of the Indian ports is because of its pricing mechanism and its ability to take proactive decision, especially with regard to capacity enhancement of the terminals. This is so because in major Indian ports, the ship pays for the number of days it stays in the berth. In inefficient ports, ships stay for long duration and as a result the port earns on account of its inefficiencies. These ports fail to recognize the paradox, and as such take corrective action only after ships divert to other ports. Ports projects have long gestation periods. So far, no study encompassing the dimensions port pricing, productivity and efficiency has been undertaken by researchers. In this article we attempt to explore the causes that affect the performance of Indian ports. We present a cause and effect analysis to explain the dynamics arising out of the interactions of productivity, infrastructure, and pricing mechanism of an Indian port system. A system dynamics framework has been used to develop the causal model. Four feedback loops were identified, which explain the governing rules and the paradoxes impacting the performance of Indian ports.